MASCEM: Optimizing the performance of a multi-agent system. (15th September 2016) - Santos, Gabriel; Pinto, Tiago; Praça, Isabel; Vale, Zita
Abstract: The electricity market sector has suffered massive changes in the last few decades. The worldwide electricity market restructuring has been conducted to potentiate the increase in competitiveness and thus decrease electricity prices. However, the complexity in this sector has grown significantly as well, with the emergence of several new types of players, interacting in a constantly changing environment. Several electricity market simulators have been introduced in recent years with the purpose of supporting operators, regulators, and the involved players in understanding and dealing with this complex environment. This paper presents a new, enhanced version of MASCEM (Multi-Agent System for Competitive Electricity Markets), an electricity market simulator with over ten years of existence, which had to be restructured in order to be able to face the highly demanding requirements that the decision support in this field requires. This restructuring optimizes the performance of MASCEM, both in results and execution time. Highlights: Optimization of an agent-based electricity market simulator. Improvement of the flexibility and capability to accommodate new market models and players. Reduction of the simulation time using intelligent and adaptive approaches. Introduction of the capability to simulate a large set of real scenarios. Interoperability with external systems to enable joint power system simulations.